Analysis of Factors Affecting International E-Wallet Use - Felicia Koo; Fendy Cuandra (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The research in this article will examine whether perceived usefulness, privacy and security of e-wallets, perceived ease of use, and perceived trust mediated by behavioral intention affect the use of e-wallets. This study uses primary data, namely data obtained by distributing questionnaires using a google form to 230 respondents. The research data is processed using the smart PLS 3 program. The results of this study are perceived usefulness, perceived ease of use, and perceived trust have a positive effect on behavioral intention and e-wallet use. For privacy and security, this variable has a positive effect on behavioral intention but has no relationship with e-wallet use. In addition, the study also found a positive relationship between behavioral intention and e-wallet use, so it can be concluded that the actual use of an e-wallet is determined by the user's intention to use it. Therefore, users should be given an understanding of this faster and easier transaction to encourage usage.